Water Pollution Control and Treatment Based on Quantum Dot Chemical and Biological High-Sensitivity Sensing - Guihua Zheng (Hindawi Limited, 2021)
Inorganic pollutants in water can have an important impact on ecosystems and human health, so the development of rapid and sensitive detection methods for typical inorganic pollutants in water samples is important for understanding the pollution status of the water environment, as well as water pollution prevention and protection of drinking water safety. Fluorescence sensing technology has the advantages of fast response, high sensitivity, simple operation, and low cost but still has the problems of low quantum yield, cumbersome construction process, and limited practical applications. Based on the excellent fluorescence properties, a series of fluorescence sensing was constructed for the rapid, highly sensitive, and selective detection of various typical inorganic pollutants in water. And the related fluorescence sensing mechanism was investigated in this paper. In this paper, nitrogen/sulfur codoped carbon quantum dots (N, S-CQDs) were prepared for the sensitive and selective detection of sulfide and ferric ion. The blue fluorescent N, S-CQDs were prepared by a one-step hydrothermal method using ammonium citrate and L-cysteine as raw materials, which have excitation wavelength dependence and fluorescence quantum yield of 16.1% for the selective detection of sulfides with a detection limit (S/N=3) of 11.0 nM (about 0.35 μg/L). CQDs with significantly higher fluorescence quantum yields (69%) and no excitation dependence were prepared when citric acid was used instead of ammonium citrate and were used for the selective detection of ferric ion with a detection limit of 14.0 nM (~0.8 μg/L). The method has been successfully applied to the determination of total phosphorus in surface water and human urine, and the fluorescence color change of the dual-emission sensing can be used for the naked-eye identification and semiquantitative detection of phosphate.